Current‐restrained DC under‐voltage protection for a bipolar HVDC system. Issue 15 (13th September 2018) - Kang, Sang‐Hee; Hwang, Chang‐Hyun
Abstract : The proposed method in this study is a current‐restrained DC under‐voltage protection for a bipolar HVDC system. In a bipolar HVDC system, the inrush phenomenon of a converter transformer can cause the DC voltage drop of the operating pole due to the sympathetic inrush. In this case, the DC under‐voltage protection relay in a bipolar HVDC system may trip the operating pole. Then the bipolar HVDC system cannot transmit any power. In order to block the ignition of an unwanted trip when the converter transformer of the not‐operating pole is energised, a current‐restrained DC under‐voltage protection method for a bipolar HVDC system is suggested. In this method, a DC harmonic current‐restraining element is used to detect an inrush phenomenon. The second harmonic component and the fundamental frequency component in the DC‐side current are used as a factor to judge the inrush phenomenon in this method. In order to discuss the proposed method, a bipolar HVDC system is modelled with CIGRE HVDC benchmark model by using PSCAD/EMTDC.